The Selected Letters of Nikos Kazantzakis - Kazantzakis, Nikos, 1883-1957 (Book collections on Project MUSE., 2012)
The life of Nikos Kazantzakis--the author of Zorba the Greek and The Last Temptation of Christ--was as colorful and eventful as his fiction. And nowhere is his life revealed more fully or surprisingly than in his letters. Edited and translated by Kazantzakis scholar Peter Bien, this is the most comprehensive selection of Kazantzakis's letters in any language. One of the most important Greek writers of the twentieth century, Kazantzakis (1883-1957) participated in or witnessed some of the most extraordinary events of his times, including both world wars and the Spanish and Greek civil wars. As.